Reshaping EU Legislation for Air Pollution Control: Main Features of the Proposed Directive in Comparison with the US Legislation - Vinceti, S. R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
In October 2022, the European Commission released a draft of a new Directive aimed at securing more effective control and prevention of outdoor air pollution in Europe through the recasting and update of previous European legislation. The proposal is intended to reshape the current regulations in the field within the EU and its implementation at the Member State level and achieve lower air pollution in light of the recent advancements in environmental health and novel indications in the field from the World Health Organization. In addition, the proposed Directive provides a legal framework for air pollution control that falls within the wider legal context of the EU Green Deal and NextGenerationEU initiatives. The new rules are also remarkably consistent with corresponding and updated US regulations, though stricter in terms of air pollution control and more open to interactions with local authorities. In sum, the proposed EU Directive appears to take better stock of the emerging scientific evidence on the adverse effects of air pollution and may provide an effective legal instrument for adequate public health protection.